2023
DOI: 10.1002/brb3.2986
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ketamine administration on chronic unpredictable stress‐induced rat model of depression during extremely low‐frequency electromagnetic field exposure: Behavioral, histological and molecular study

Abstract: Objectives: In the study, we examined the effects of ketamine and extremely low-frequency electromagnetic fields (ELF-EMF) on depression-like behavior, learning and memory, expression of GFAP, caspase-3, p53, BDNF, and NMDA receptor in animals subjected to chronic unpredictable stress (CUS). Methods:After applying 21 days of chronic unpredictable stress, male rats received intraperitoneal (IP) of ketamine (5 mg/kg) and then were exposed to ELF-EMF (10-Hz, 10-mT exposure conditions) for 3 days (3 h per day) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 110 publications
0
2
0
Order By: Relevance
“…It was revealed that combining treatment of ELF-EMF and ketamine increased depression-like behavior, degenerated hippocampal and cortical pyramidal neurons. Furthermore, decreased BDNF and increased caspase-3 levels were also confirmed ( Salari et al, 2023 ). The beneficial effect of (2R,6R)-hydroxynorketamine [(2R,6R)-HNK], a metabolite of ketamine, has been also demonstrated.…”
Section: Role Of Bdnf-related Intracellular Signaling In Action Of An...mentioning
confidence: 90%
See 1 more Smart Citation
“…It was revealed that combining treatment of ELF-EMF and ketamine increased depression-like behavior, degenerated hippocampal and cortical pyramidal neurons. Furthermore, decreased BDNF and increased caspase-3 levels were also confirmed ( Salari et al, 2023 ). The beneficial effect of (2R,6R)-hydroxynorketamine [(2R,6R)-HNK], a metabolite of ketamine, has been also demonstrated.…”
Section: Role Of Bdnf-related Intracellular Signaling In Action Of An...mentioning
confidence: 90%
“…Remarkably, it has been suggested that combining low-frequency electromagnetic fields (ELF-EMF) and ketamine, which are recognized as effective treatment against depression-like behavior, respectively, has adverse effects ( Salari et al, 2023 ). Salari et al (2023) performed behavioral, histological and molecular study using male rats received ketamine treatment and/or ELF-EMF following 3 weeks chronic unpredictable stress. It was revealed that combining treatment of ELF-EMF and ketamine increased depression-like behavior, degenerated hippocampal and cortical pyramidal neurons.…”
Section: Role Of Bdnf-related Intracellular Signaling In Action Of An...mentioning
confidence: 99%